Imaging Carrier Dynamics and Transport in Hybrid Perovskites with Transient Absorption Microscopy. Issue 26 (18th February 2020) - Deng, Shibin; Blach, Daria D.; Jin, Linrui; Huang, Libai
Abstract: In this review, the recent progress in using transient absorption microscopy to image charge transport and dynamics in semiconducting hybrid organic–inorganic perovskites is discussed. The basic principles, instrumentation, and resolution of transient absorption microscopy are outlined. With temporal resolution as high as 10 fs, sub‐diffraction‐limit spatial resolution, and excited‐state structural resolution, these experiments have provided crucial details on charge transport mechanisms that have been previously obscured in conventional ultrafast spectroscopy measurements. Morphology‐dependent mapping unveils spatial heterogeneity in carrier recombination and cooling dynamics. By spatially separating the pump and probe beams, carrier transport across grain boundaries has been directly visualized. Further, femtosecond temporal resolution allows for the examination of nonequilibrium transport directly, revealing extraordinarily long‐range hot carrier migration. The application of transient absorption microscopy is not limited to hybrid perovskites but can also be useful for other polycrystalline materials in which morphology plays an important role in carrier transport. Abstract : Carrier transport and recombination are critical processes in determining solar cell efficiency. Perovskite materials, a new class of semiconductors, are very promising alternatives to silicon because of their extreme low cost and ease of fabrication. This review highlights the recent progress in imaging carrier migration and dynamics in hybrid perovskites using methods that combine optical imaging with ultrafast laser spectroscopy.